(untitled) (ModaPalavra e-periódico, 2021)
This article presents the main results of an investigation developed on the Professional Master Degree in Design and describes the productive processes used at the textiles industries, specifically in their primary and secondary sections. The main objective of the research project was to analyze the productive processes of circular knitted fabrics largely used in the Brazilian industry, from the cotton cultivation to the improvement/finish techniques of the products, pointing out environmental effects, in order to compare the procedures and the fabric classification. The applied methodology contains theoretical information, field research–in order to gather the data–, data analysis and the development of a table. The more important results are about the ecological indexes of the cotton fabric classification when it comes to the environmental impact, presented in the table. The article tries to spread the knowledge concerning conscious consumption about the textile and clothing products.